The Moderating Role of Individual Adaptability in the Leadership Effectiveness Model: A Conceptual Paper - Albert, Apoi; Hamrila, Abdul Latif; Azzie Joyce, Takong (Human Resource Management Academic Research Society, 2021)
Leadership effectiveness has been the subject of interest by researchers over the years. While transformational leadership and employee reactions have been strongly associated with leadership effectiveness, individual adaptability has also become increasingly important in the current working environment, which demands employees to apply creative, innovative, collaborative, and analytical skills that technology cannot replicate. Although studies on individual adaptability have focused on culture and unfamiliar environment, there are scarce findings on individual adaptability in the context of skills. For this reason, the present study extends the existing literature on individual adaptability in order to measure the impacts of these skills on the links between transformational leadership and employee reactions with individual work performance. To further explicate and extend the current leadership effectiveness model,the expectancy theory of motivation is applied in this study and the researchers also suggest that individual adaptability moderates the relationships between transformational leadership and employee reactions with individual work performance. Therefore, this paper contributes to the literature by developing a leadership effectiveness model of individual work performance by incorporating skills as the new measurements for individual adaptability as a moderator in the present study.